Controlling carbon nanofibre morphology for improved composite reinforcement. (22nd September 2009) - Atwater, Mark; Leseman, Zayd C.; Phillips, Jonathan
Carbon nanofibres were grown at low temperatures on a novel fibre catalyst, palladium particles, using a novel method, growth in fuel rich combustion conditions. The growth of carbon filaments by this process was found to be remarkably rapid. Preliminary analysis of how changes in operating parameters, for example gas flow rate and reactant ratio, showed that fibre diameter and other factors such as helicity are very sensitive to the precise conditions employed, suggesting simple means to impact overall properties of the fibres. The ability to control diameter, helicity, and surface roughness are discussed with possible importance to advanced composites.